ADVANCED THEORIES IN COMMUNICATION: A CLINICAL SOCIOLOGY APPROACH - Rheaume, Jacques (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The specific contribution of a clinical sociological approach to communication, a multi- disciplinary field of study, is considered in this course. Different theories, models, and practices are reviewed, particularly those coming from a psycho- sociological perspective. For example, the course will include topics, such as the theory and practice of social intervention; interpersonal relationships; small group dynamics; organizational studies; social networks; and social representation.